Система водопостачання мікрорайону "Троянда" у м. Кропивницький Кіровоградської обл. з аналізом можливості використання дощового стоку - Кравець, Тарас Володимирович; Kravets, Taras Volodymyrovych (Національний університет "Львівська політехніка", 2024)
Магістерську кваліфікаційну роботу виконано на підставі завдання, виданого кафедрою гідротехніки та водної інженерії, діючих в Україні державних нормативних документів [1, 2], а також довідкових матеріалів з водовідведення. Розроблено проект системи водопостачання мікрорайону "Троянда" у м. Кропивницький Кіровоградської обл. з аналізом можливості використання дощового стоку. На основі аналізу запроектовано систему водопостачання водою мікрорайону з підземних джерел. Проектом передбачається вісім водопідйомнмх свердловин потужністью 7 м3/добу кожна. Свердловини обладнання свердловинними насосами Grundfos марки SP7-17. Над свердловиною влаштовуються підземні будівлі так звані насосні станції першого підйому з дотримання усіх будівельних норм і правил. Від свердловин вода по поліетиленовим трубам діаметром 75мм SDR17 з’єднується в загальний колектор і загальним колектором подають воду в резервуари запасу води. Резервуари круглі в плані, наземні, забезпечують ефективне накопичення та регулювання подачі води. Вони оснащені підвідними, відвідними та переливними трубопроводами, що гарантують стабільний рух води та її резервування. Система переливних патрубків дозволяє запобігати надмірному підвищенню рівня води, забезпечуючи її контрольований відтік у випадку переповнення резервуару. Це сприяє безпечній експлуатації та попередженню аварійних ситуацій. Для підтримання якості води резервуари обладнані сучасними вентиляційними системами та теплоізоляцією, що мінімізує вплив зовнішніх факторів та захищає воду від забруднень. Перед подачею в резервуари вода проходить систему водопідготовки. Процес водопідготовки базується на аналізі якості води у джерелі водопостачання. Підбір відповідних методів очищення, склад та параметри водопідготовчих установок, а також необхідні дози реагентів, визначаються залежно від хімічного і бактеріологічного складу вихідної води. У цьому випадку джерелом водопостачання є підземні води, які, як правило, характеризуються стабільним хімічним складом та нижчим рівнем забруднення, ніж поверхневі води. Основні методи це знезараження води гіпохлоритом натрію. Дозування відбувається дозуючими насосами безпосередньо в трубопровід перед резервуарами запасу води. Насосною станцією II-го підйому вода подається споживачам. Насосна станція підвищення тиску є сучасною енергоефективною інженерною спорудою, що забезпечує стабільне водопостачання споживачів. Вона оснащена шафою керування із частотними перетворювачами, які дозволяють здійснювати плавне регулювання параметрів роботи насосів залежно від потреб водоспоживання. Це забезпечує економію електроенергії, зменшення гідравлічних ударів у системі та підвищення загальної надійності обладнання. Насосна станція автоматизована та інтегрована в систему диспетчеризації, що дозволяє контролювати всі основні параметри в реальному часі. Вона працює в оптимальному режимі, забезпечуючи безперебійне постачання води із необхідним тиском і витратою. Марка насосної станції другого підйому Hydro MPC-E-3 CRE15-5 фірми Grundfos. Магістральний трубопроводи виконані з поліетилену, що забезпечує їхню довговічність, корозійну стійкість та надійність у експлуатації. Поліетиленові труби мають високу гнучкість, що дозволяє компенсувати температурні деформації та зменшувати ризик пошкодження при гідравлічних ударах. Діаметр магістального трубопровода ПЕ 280 SDR17. Визначено витрату води на водопостачання мікрорайону. Виконано гідравлічний розрахунок водопровідної мережі. Як результат, встановлено діаметри водопровідних труб. Зображені профіля мереж водопостачання. Зроблено техніко-економічне порівняння будівництва мережі. Визначено: витрати на електроенергію, величина амортизаційних відрахувань, витрати на поточний ремонт, заробітну плату обслуговуючого персоналу. Також, у рамках наукової частини роботи, було проведено дослідження використання дощового стоку. Об’єкт дослідження – водопровідна мережа м. Кропивницький Кіровоградської обл Предмет дослідження – гідравлічний режим роботи системи водопостачання міста м. Кропивницький Кіровоградської обл. Мета дослідження: визначення розрахункових витрат господарсько- питних вод, діаметрів основних водопровідних колекторів, розрахунок водопровідної насосної станції першого і другого підйому, методи знезараження води, складання локальних кошторисів на загально будівельні роботи. Результати дослідження. 1. Запроектовано господарсько-питну систему водопровідної мережі. 2. Визначено розрахункові витрати господарсько-питних вод. 3. Проведено гідравлічний розрахунок господарсько-питної водопровідної мережі. 4. Запроектовано водопровідну насосну станцію першого і другого підйому (визначено продуктивність станції та напір насосів, підібрано насоси). 5. Проведено дослідження методів знезараження водопровідних вод. 6. Складено локальні кошториси на загальнобудівельні роботи.діаметр трубопроводу, насосна станція, знезараження вод.

The master's qualification work was carried out on the basis of the assignment issued by the Department of Hydraulic and Water Engineering, state regulatory documents in force in Ukraine [1, 2], as well as reference materials on drainage. A project for the water supply system of the microdistrict "Troyanda" in the city of Kropyvnytskyi, Kirovohrad region, has been developed with an analysis of the possibility of using rainwater. Based on the analysis, a water supply system for the microdistrict from underground sources has been designed. The project provides for eight water-lifting wells with a capacity of 7 m3/day each. The wells are equipped with Grundfos SP7-17 well pumps. Underground buildings, so-called first-stage pumping stations, are constructed above the well in compliance with all building codes and regulations. From the wells, water is connected to a common collector through polyethylene pipes with a diameter of 75mm SDR17, and water is supplied to the water storage tanks through the common collector. The tanks are circular in plan, above-ground, and provide efficient storage and regulation of water supply. They are equipped with supply, discharge, and overflow pipelines, which guarantee stable water movement and its reserve. The overflow pipe system prevents excessive water level increase, ensuring its controlled outflow in case of tank overflow. This contributes to safe operation and prevention of emergency situations. To maintain water quality, the tanks are equipped with modern ventilation systems and thermal insulation, which minimizes the impact of external factors and protects the water from pollution. Before being fed into the tanks, the water passes through a water treatment system. The water treatment process is based on the analysis of the quality of the water at the water supply source. The selection of appropriate treatment methods, the composition and parameters of the water treatment plants, as well as the required doses of reagents, are determined depending on the chemical and bacteriological composition of the source water. In this case, the source of water supply is groundwater, which is usually characterized by a stable chemical composition and a lower level of pollution than surface water. The main methods are water disinfection with sodium hypochlorite. Dosing is done by dosing pumps directly into the pipeline in front of the water storage tanks. The second-stage pumping station supplies water to consumers. The pressure boosting pumping station is a modern energy-efficient engineering structure that ensures a stable water supply to consumers. It is equipped with a control cabinet with frequency converters that allow smooth adjustment of pump operation parameters depending on water consumption needs. This ensures energy savings, reduces water hammer in the system and increases the overall reliability of the equipment. The pumping station is automated and integrated into the dispatching system, which allows you to monitor all the main parameters in real time. It operates in optimal mode, ensuring uninterrupted water supply with the required pressure and flow rate. The brand of the second lift pumping station is Hydro MPC-E-3 CRE15-5 from Grundfos. The main pipelines are made of polyethylene, which ensures their durability, corrosion resistance and reliability in operation. Polyethylene pipes have high flexibility, which allows them to compensate for temperature deformations and reduce the risk of damage during water hammer. The diameter of the main pipeline is PE 280 SDR17. The water consumption for the water supply of the microdistrict was determined. A hydraulic calculation of the water supply network was performed. As a result, the diameters of the water pipes were established. The profiles of the water supply networks were depicted. A technical and economic comparison of the network construction was made. The following were determined: electricity costs, depreciation charges, maintenance costs, and maintenance personnel salaries. Also, as part of the scientific part of the work, a study of the use of rainwater was conducted. Research Object – The water supply network of Kropyvnytskyi, Kirovohrad region. Research Subject – The hydraulic operating mode of the city's water supply system in Kropyvnytskyi, Kirovohrad region. Research Objective – Determining the calculated consumption of domestic drinking water, the diameters of the main water pipelines, the calculation of the first and second-stage water pumping stations, methods of water disinfection, and the preparation of local estimates for general construction works. Research Results: 1. The domestic drinking water supply system has been designed. 2. The calculated consumption of domestic drinking water has been determined. 3. A hydraulic calculation of the domestic drinking water supply network has been carried out. 4. A water pumping station for the first and second stages has been designed (the station’s capacity and pump pressure have been determined, and the pumps have been selected). 5. Research on methods of water disinfection has been conducted. 6. Local estimates for general construction works have been prepared.
Water supply system of the "Troyanda" residential district in Kropyvnytskyi, Kirovohrad Region with an analysis of the possibility of using rainwater runoff
Keywords: 3.192.00.00; витрата; напір; стічні води; водопровідний колектор; consumption; pressure; wastewater; water pipeline collector; pipeline diameter; pumping station; water disinfection. List of referenced literature sources: DBN V.2.5-74:2013. Water supply. External networks and structures. Basic design principles. Ministry of Regional Development; Construction; and Housing and Communal Services of Ukraine; 2013. 1. DBN V.2.5-64:2012. Internal water supply and sewerage. Part I: Design. Part II: Construction. – Kyiv: Ministry of Regional Development of Ukraine; 2013. – 105 pages. 2. External gravity drainage networks made of double-layer plastic pipes with a structured wall. Design and construction manual / V.M. Zhuk; M.I. Stasiuk; O.O. Matsiievska; O.T. Vozniak – Company "Elplast"; Lviv Polytechnic National University; 2005. – 52 pages. 3. Shevelev F.A. Tables for hydraulic calculation of steel; cast iron; asbestos cement; plastic; and glass water pipes. – Moscow: Stroyizdat; 1973. 4. Protsyk S.I. Basics of economic systems of city engineering equipment: Educational manual. – Kyiv: NMC VO; 1991. – 312 pages. 5. Water supply. Water intake structures. Tugay A.M. – Kyiv: Higher School; Main Publishing House; 1984. – 200 pages. 6. Water Supply / A.Y. Naimanov; S.B. Nikisha; N.G. Nasonkina; et al. – Donetsk: Nord-Press; 2004. – 649 pages